A general view of the localization of apps for mobile devices: status, challenges and trends. Formats and customary processes in the translation of iOS and Android apps - Eduard Simón Jiménez (Revista Tradumàtica, 2016)
Given the exponentially quickening inrush of mobile devices into our lives, predicting even the near-term evolution of this trend may be audacious, but is still essential. With this challenge in mind, this article tries to thresh out the scenarios that localization professionals may face when catching up with the latest trends on localization for mobile devices. Specifically, it details a typology of localization-industry clients and projects while exploring the processes and the most common formats involved. The author presents different categories of projects involving standard formats or complete Android or iOS apps.